2023
DOI: 10.1021/jacs.3c07488
|View full text |Cite
|
Sign up to set email alerts
|

Quantification of Binding of Small Molecules to Native Proteins Overexpressed in Living Cells

Yuwen Yin,
Serena Li Zhao,
Digamber Rane
et al.

Abstract: The affinity and selectivity of small molecules for proteins drive drug discovery and development. We report a fluorescent probe cellular binding assay (FPCBA) for determination of these values for native (untagged) proteins overexpressed in living cells. This method uses fluorophores such as Pacific Blue (PB) linked to cell-permeable protein ligands to generate probes that rapidly and reversibly equilibrate with intracellular targets, as established by kinetic assays of cellular uptake and efflux. To analyze … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
6
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1
1

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(6 citation statements)
references
References 85 publications
(151 reference statements)
0
6
0
Order By: Relevance
“…Consequently, as an important parameter, binding affinity constant (š¾ ) has been a valuable in vitro measure for various preclinical evaluation, including the selection of lead compounds, the optimization of leads, and the predictions of in vivo potency, pharmacokinetic properties and safely profiles [5]. Therefore, it is of great important to obtain accurate š¾ values of the inhibitors.…”
Section: š¾ = [ ][ ]mentioning
confidence: 99%
“…Consequently, as an important parameter, binding affinity constant (š¾ ) has been a valuable in vitro measure for various preclinical evaluation, including the selection of lead compounds, the optimization of leads, and the predictions of in vivo potency, pharmacokinetic properties and safely profiles [5]. Therefore, it is of great important to obtain accurate š¾ values of the inhibitors.…”
Section: š¾ = [ ][ ]mentioning
confidence: 99%
“…As an alternative method for studies of target engagement, we recently reported the fluorescent probe cellular binding assay (FPCBA). This new method uses flow cytometry for quantitative studies of the binding of cell-permeable fluorescent probes and competitors to specific native (untagged) proteins that are overexpressed in living cells.…”
mentioning
confidence: 99%
“…This new method uses flow cytometry for quantitative studies of the binding of cell-permeable fluorescent probes and competitors to specific native (untagged) proteins that are overexpressed in living cells. Although FPCBA was previously validated using allosteric activators of Protein Kinase C isozymes, our previous studies āˆ’ of interactions of fluorescent derivatives of the anticancer drug paclitaxel (Taxol) with microtubules in living cells were instrumental in developing this method. Key to this approach is the use of cell-permeable fluorophores that can be efficiently detected by flow cytometry when linked to ligands of protein targets.…”
mentioning
confidence: 99%
See 2 more Smart Citations